2018
DOI: 10.1136/archdischild-2017-314094
|View full text |Cite
|
Sign up to set email alerts
|

Eleven years of retinopathy of prematurity in one neonatal intensive care unit in Jakarta, Indonesia

Abstract: The total incidence of ROP as well as severe ROP in infants with a BW of <1000 g and 1000-1500 g in our NICU is higher than in a developed country. ROP in Indonesia is also seen in infants with a BW of 1500-2500 g. Increasing the awareness of the risks of oxygen as well as better equipment to monitor oxygen delivery is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…As a reference in this paper, we used data from one referral hospital as well as data from the literature. The rates of ROP found in one hospital in Indonesia 1 and the studies done in other centres 2 all showed a high incidence of ROP in the period before 2015. Therefore, we are convinced that the incidence of ROP was indeed much higher than suggested by the results of this survey.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As a reference in this paper, we used data from one referral hospital as well as data from the literature. The rates of ROP found in one hospital in Indonesia 1 and the studies done in other centres 2 all showed a high incidence of ROP in the period before 2015. Therefore, we are convinced that the incidence of ROP was indeed much higher than suggested by the results of this survey.…”
Section: Discussionmentioning
confidence: 74%
“…1 2 In that previous period, we found in one NICU a 40% incidence of all-stage ROP in infants below 28 weeks and a 28% incidence in the group aged 28-32 weeks. 1 Other studies from the period 2005-2015 in Indonesia found a ROP incidence of 18%-30% in infants born before 32 weeks and/or with a birth weight of less than 1500 g. 2 Different factors may have contributed to this marked decline in ROP. First, a national guideline for ROP prevention and screening was published in 2010.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the studies on ROP conducted in Indonesia and other literature, 3‐5,61,62 we propose the following guideline to prevent and screen preterm infants for ROP. The abbreviation “R1O2P3” is used to facilitate the procedures that must be standard practice in all perinatal/neonatal units (Figure 3).…”
Section: Stop: R1o2p3mentioning
confidence: 99%
“…56,57,59,60 In all HIC guidelines, laser treatment is the first treatment; second is intra-vitreal injection with anti-vascular endothelial growth factor (VEGF). This intervention might cause more myopia later, and there is doubt about its safety for disturbed angiogenesis in other Based on the studies on ROP conducted in Indonesia and other literature, [3][4][5]61,62 we propose the following guideline to prevent and screen preterm infants for ROP. The abbreviation "R1O2P3" is used to facilitate the procedures that must be standard practice in all perinatal/neonatal units (Figure 3).…”
Section: Rop Treatmentmentioning
confidence: 99%
See 1 more Smart Citation